Method for preparing 5N high-purity quartz sand by using mica pegmatite
Patent Information
- Application Number
- CN202410346536.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-26
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-26
AI Technical Summary
但目前传统热处理法常伴随着以下固有缺点:1)能耗大:在传统的煅烧工艺中,通常需要电阻炉将石英砂加热至800~1500℃,保温时间在1~24h
[0026]本发明利用液氮急冷后快速解冻的方法代替传统的热处理法使石英颗粒及其包裹体破碎并产生裂隙,整个过程能耗更低、操作更安全且对环境影响更小。且利用小分子酸浸出及硝酸作为氧化剂辅助浸出同时加入阳离子捕获剂酸洗,极大地增加了提纯效率。本发明方法简单,可控性强,容易实现规模化生产,具有实用性。
Smart Images

Figure CN118343997B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of quartz processing and purification technology, specifically relating to a method for preparing 5N high-purity quartz sand using mica pegmatite. Background Technology
[0002] Quartz is an important mineral resource with very stable physical and chemical properties. High-purity quartz ore can contain over 99.95% silica. It is a primary raw material for producing high-end products such as quartz glass and quartz crucibles. Quartz glass made from high-purity quartz exhibits characteristics such as high temperature resistance, low coefficient of thermal expansion, high insulation, corrosion resistance, and high luminous transmittance. Its high comprehensive performance makes it an indispensable material in high-tech industries such as semiconductors, optical devices, optical communications, and solar energy. Although my country has abundant quartz resources, the presence of elemental impurities and inclusions makes it difficult to achieve the level of high-purity quartz sand. High-purity quartz sand of 4N8 and above is heavily reliant on imports.
[0003] Currently, the preparation of high-purity quartz mainly relies on the purification of natural crystal, but compared to quartz resources, natural crystal resources are relatively scarce. Pegmatite, named for its frequent presence of large crystals, is rich in quartz and is widely distributed in my country. Using pegmatite to replace natural crystal in the preparation of high-purity quartz sand can effectively fill the domestic demand for high-purity quartz sand. Mica minerals are the main associated minerals in quartz mining; the presence of mica and other minerals severely affects the quality of quartz products, leading to an increase in the content of elements such as aluminum, iron, and potassium in the quartz. Therefore, mica pegmatite needs further purification to meet usage requirements.
[0004] Currently, heat treatment is an important method for purifying high-purity quartz. It includes high-temperature cracking and chlorination roasting, primarily based on calcination, combined with water quenching. Utilizing the thermal effect and the difference in thermal expansion coefficients between different ores, the raw ore is broken up, exposing impurities to the surface for subsequent acid leaching, magnetic separation, flotation, and other operations. However, traditional heat treatment methods often have the following inherent drawbacks: 1) High energy consumption: In traditional calcination processes, a resistance furnace is typically required to heat the quartz sand to 800–1500℃, holding it at that temperature for 1–24 hours. High temperatures and long holding times usually result in significant energy consumption. 2) High cost: High energy consumption and the management and maintenance of high-temperature treatment equipment increase operating costs. 3) Complex process and high operational risk: Heat treatment is a high-temperature operation, which inherently carries certain operational risks. Furthermore, the complex heat treatment process presents certain safety hazards. For example, water quenching involves rapidly quenching the quartz sand immediately after high-temperature roasting, which can easily lead to safety accidents; chlorination roasting produces harmful exhaust gases, polluting the environment.
[0005] Traditional heat treatment processes are accompanied by problems such as high energy consumption, high cost, and high operational risks, and it is ultimately difficult to achieve a purity of ≥99.99% for 4N high-purity quartz sand. Summary of the Invention
[0006] In view of this, the purpose of this invention is to provide a method for preparing 5N high-purity quartz sand using mica pegmatite. This method is simple, low-cost, highly controllable, and can produce 5N high-purity quartz sand.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] This invention provides a method for preparing 5N high-purity quartz sand using mica pegmatite, comprising the following steps:
[0009] The first slurry provides raw mica pegmatite powder, and the pH value of the first slurry is 2 to 3;
[0010] The first ore slurry is subjected to a first flotation using a first cation capture agent to obtain a first impurity-removed ore slurry;
[0011] After adjusting the pH value of the first impurity-removed slurry to 7-8, the first impurity-removed slurry after pH adjustment is subjected to a second flotation using an anion capture agent to obtain mica pegmatite concentrate;
[0012] After the mica pegmatite concentrate is adjusted into a second slurry, it is sequentially subjected to liquid nitrogen rapid cooling and thawing to obtain rapidly cooled mica pegmatite concentrate.
[0013] The rapidly cooled mica pegmatite concentrate, acid solution, and second cation capture agent are mixed and subjected to acid leaching to obtain the acid leaching product; the acid solution includes hydrofluoric acid, hydrochloric acid, and nitric acid;
[0014] The acid leaching product was washed sequentially until neutral, then subjected to solid-liquid separation and solid drying to obtain 5N high-purity quartz sand.
[0015] Preferably, the first cation scavenger is dodecylamine acetate; the amount of dodecylamine acetate added relative to the first slurry is 300-500 g / t.
[0016] Preferably, the anion scavenger is sodium octadecenoate; the amount of sodium octadecenoate added relative to the first impurity-removing slurry after pH adjustment is 100-200 g / t.
[0017] Preferably, the volume ratio of liquid nitrogen to the second slurry is 1.5 to 4:1.
[0018] Preferably, the liquid nitrogen quenching time is 24–48 hours.
[0019] Preferably, the pickling temperature is 50–80°C, and the pickling time is 4–12 hours.
[0020] Preferably, the liquid-to-solid ratio of the slurry obtained by mixing the rapidly cooled mica pegmatite concentrate, acid, and second cation capture agent is 2 to 4:1.
[0021] Preferably, the particle size of the mica pegmatite ore powder is 70–300 μm.
[0022] Preferably, the mass percentage of mica pegmatite powder in the first slurry is 10-30%.
[0023] Preferably, the mass ratio of the anion scavenger to the first cation scavenger is 1:1.5 to 3.
[0024] This invention provides a method for preparing 5N high-purity quartz sand using mica pegmatite, comprising the following steps: providing a first slurry of raw mica pegmatite powder, the first slurry having a pH value of 2-3; performing a first flotation on the first slurry using a first cation scavenger to obtain a first impurity-removed slurry; adjusting the pH value of the first impurity-removed slurry to 7-8, and then performing a second flotation on the pH-adjusted first impurity-removed slurry using an anion scavenger to obtain mica pegmatite concentrate; adjusting the mica pegmatite concentrate into a second slurry, and then sequentially subjecting it to liquid nitrogen rapid cooling and thawing to obtain rapidly cooled mica pegmatite concentrate; mixing the rapidly cooled mica pegmatite concentrate, acid solution, and a second cation scavenger, and performing acid washing treatment to obtain an acid-washed leaching product; the acid solution comprising hydrofluoric acid, hydrochloric acid, and nitric acid; and sequentially washing the acid-washed leaching product to neutrality, performing solid-liquid separation, and solid drying to obtain 5N high-purity quartz sand.
[0025] This invention uses mica pegmatite as raw material, performs two-stage flotation on the mica pegmatite, and adjusts the pH value to allow OH- to be released. - or H +The distribution of quartz on the surface of mica pegmatite changes, causing it to become charged. In the first stage of flotation, the pulp is adjusted to acidic conditions before adding a cationic scavenger. The negatively charged mica surface effectively increases the adsorption concentration of the scavenger, while the neutral quartz surface reduces electrostatic adsorption with the scavenger, retaining it as much as possible within the flotation cell and minimizing quartz loss. In the second stage of flotation, the pulp is adjusted to neutral or slightly alkaline conditions (7-8) before adding an anionic scavenger to further remove Ti and Fe ions from the first stage flotation, thus purifying the mica pegmatite ore. After obtaining the mica pegmatite concentrate, it is prepared into a pulp and rapidly thawed in liquid nitrogen. During this rapid thawing process, the quartz particles, impurity mineral inclusions, and gas-liquid inclusions are affected by factors such as cold contraction and thermal expansion. The quartz particles break apart, exposing impurities in the crystal lattice, while the inclusions expand and rupture, exposing impurities within the inclusions and causing some to vaporize and diffuse out of the quartz crystal lattice. During this process, numerous fissures are generated on the surface and inside of the quartz particles, providing conditions for increasing the contact area of the quartz particles during subsequent acid washing. Acid washing with small-molecule acids such as hydrofluoric acid allows hydrogen ions and anions to diffuse along the fissures in the fractured quartz sample into the grain boundaries of the quartz crystals, reacting chemically with impurity minerals and dissolving and diffusing metal ions into the solution. The addition of HNO3 as an oxidant assists in the leaching of metal oxides. Simultaneously, a cation scavenger is added during the acid washing process. This cation scavenger contacts the quartz particles, which have a larger contact area, thereby capturing more Na, K, and Li ions. Finally, after solid-liquid separation, water washing, and drying, the quartz sand is purified.
[0026] This invention utilizes a rapid thawing method following liquid nitrogen quenching to replace traditional heat treatment, breaking down quartz particles and their inclusions and creating fissures. The entire process consumes less energy, is safer, and has less environmental impact. Furthermore, the use of small-molecule acid leaching and nitric acid as an oxidizing agent to assist leaching, along with the addition of a cation-scavenging agent for acid washing, significantly increases purification efficiency. This invention is simple, highly controllable, easily scalable, and practical.
[0027] This invention prepares 5N high-purity quartz sand with SiO2 content ≥99.999% from mica pegmatite with low SiO2 content, which increases the economic added value of mica pegmatite ore and improves its utilization rate. Attached Figure Description
[0028] Figure 1 This is a flowchart of the method for preparing 5N high-purity quartz sand using mica pegmatite according to the present invention. Detailed Implementation
[0029] This invention provides a method for preparing 5N high-purity quartz sand using mica pegmatite, comprising the following steps:
[0030] The first slurry provides raw mica pegmatite powder, and the pH value of the first slurry is 2 to 3;
[0031] The first ore slurry is subjected to a first flotation using a first cation capture agent to obtain a first impurity-removed ore slurry;
[0032] After adjusting the pH value of the first impurity-removed slurry to 7-8, the first impurity-removed slurry after pH adjustment is subjected to a second flotation using an anion capture agent to obtain mica pegmatite concentrate;
[0033] After the mica pegmatite concentrate is adjusted into a second slurry, it is sequentially subjected to liquid nitrogen rapid cooling and thawing to obtain rapidly cooled mica pegmatite concentrate.
[0034] The rapidly cooled mica pegmatite concentrate, acid solution, and second cation capture agent are mixed and subjected to acid leaching to obtain the acid leaching product; the acid solution includes hydrofluoric acid, hydrochloric acid, and nitric acid;
[0035] The acid leaching product was washed sequentially until neutral, then subjected to solid-liquid separation and solid drying to obtain 5N high-purity quartz sand.
[0036] Unless otherwise specified, the present invention does not have special requirements on the source of the raw materials used in the preparation, and commercially available products well known to those skilled in the art can be used.
[0037] The present invention provides a first slurry of mica pegmatite powder, wherein the pH value of the first slurry is 2 to 3.
[0038] In this invention, the particle size of the mica pegmatite ore powder is preferably 70-300 μm, more preferably 75-250 μm, and most preferably 100-200 μm.
[0039] In this invention, the preferred method for preparing the mica pegmatite ore powder includes the following steps: crushing, grinding and sieving the mica pegmatite ore in sequence to obtain mica pegmatite ore powder.
[0040] In this invention, the crushing equipment is preferably a jaw crusher; the grinding is preferably a grinding process; the grinding equipment is preferably a planetary ball mill; this invention does not have any special limitations on the screening process, and the sieving method well known in the art can be used to obtain the mica pegmatite raw ore powder within the above particle size range.
[0041] In this invention, the preferred method for preparing the first slurry of the mica pegmatite ore powder is to mix the mica pegmatite ore powder with water to form a slurry, thereby obtaining the first slurry; and to adjust the pH value of the first slurry to 2-3.
[0042] In this invention, the mass percentage of mica pegmatite powder in the first slurry is preferably 10-30%, more preferably 20-30%; the water is preferably ultrapure water; and the slurry preparation time is preferably 3-10 min, more preferably 5 min.
[0043] In this invention, the pH value of the first slurry is 2 to 3, preferably 2 to 2.5; the reagent used to adjust the pH value of the first slurry is preferably a sulfuric acid solution; the mass concentration of the sulfuric acid solution is preferably 5 to 15%, more preferably 10%.
[0044] After obtaining the first slurry, the present invention uses a first cation capture agent to perform a first flotation on the first slurry to obtain a first impurity-removed slurry.
[0045] In this invention, the first cation scavenger is preferably dodecylamine acetate; the amount of dodecylamine acetate added relative to the first slurry is preferably 300-500 g / t, more preferably 350-450 g / t.
[0046] In this invention, the equipment used for the first flotation is preferably a hanging tank flotation machine; the first flotation process is preferably followed by frothing after stirring; the stirring speed is preferably 1000-2000 rpm, more preferably 1200-1500 rpm; the stirring time is preferably 2-5 min, more preferably 3-4 min; the frothing is preferably performed manually with a scraper; the frothing time is preferably 2-5 min, more preferably 2-4 min.
[0047] This invention removes mica tailings from mica pegmatite ore through a first flotation process.
[0048] After obtaining the first impurity-removed slurry, the present invention adjusts the pH value of the first impurity-removed slurry to 7-8, and then uses an anion capture agent to perform a second flotation on the first impurity-removed slurry after adjusting the pH value to obtain mica pegmatite concentrate.
[0049] In this invention, the pH value of the first impurity-removed slurry is adjusted to 7-8, preferably 7.5-8; the reagent used to adjust the pH value of the first impurity-removed slurry is preferably a sodium hydroxide solution; the mass concentration of the sodium hydroxide solution is preferably 5-15%, more preferably 10%.
[0050] In this invention, the anion scavenger is preferably sodium octadecenoate; the amount of sodium octadecenoate added relative to the first impurity removal slurry after pH adjustment is preferably 100-200 g / t, more preferably 120-175 g / t.
[0051] In this invention, the mass ratio of the anion scavenger to the first cation scavenger is preferably 1:1.5 to 3, more preferably 1:2 to 3.
[0052] In this invention, the equipment used for the second flotation is preferably a hanging tank flotation machine; the second flotation process is preferably agitation followed by skimming; the agitation rate is preferably 1000-2000 rpm, more preferably 1500 rpm; the agitation time is preferably 2-5 min, more preferably 3 min; the skimming is preferably done manually with a scraper; the skimming time is preferably 2-5 min, more preferably 2 min.
[0053] This invention removes ilmenite tailings from mica pegmatite ore using a second flotation process.
[0054] After the second flotation is completed, the present invention preferably performs water washing, solid-liquid separation and solid drying on the slurry after the second flotation to obtain mica pegmatite concentrate.
[0055] In this invention, the water washing is preferably neutral; the drying temperature is preferably 60-80°C, more preferably 70-80°C; the drying time is preferably 12-48 hours, more preferably 24-36 hours; the solid-liquid separation is preferably filtration; this invention does not have any special limitation on the filtration, and any filtration process well known in the art can be used.
[0056] This invention uses mica pegmatite as raw material, performs two-stage flotation on the mica pegmatite, and adjusts the pH value to allow OH- to be released. - or H + The distribution of ions on the surface of mica pegmatite changes, causing its surface to become charged. In the first stage of flotation, after adjusting the pulp to acidic conditions, a cationic scavenger is added. The negatively charged mica surface effectively increases the adsorption concentration of the cationic scavenger, while the neutral quartz surface reduces electrostatic adsorption with the cationic scavenger, retaining it as much as possible in the flotation cell and minimizing the loss of quartz raw materials. In the second stage of flotation, after adjusting the pulp to neutral or slightly alkaline conditions (7-8), anionic scavengers are added to further remove Ti, Fe, and other ions from the first stage flotation, thereby purifying the mica pegmatite ore.
[0057] After obtaining the mica pegmatite concentrate, the present invention adjusts the mica pegmatite concentrate into a second slurry, and then sequentially performs liquid nitrogen rapid cooling and thawing to obtain rapidly cooled mica pegmatite concentrate.
[0058] In this invention, the mass percentage of mica pegmatite concentrate in the second slurry is preferably 10-30%, more preferably 20-30%; the preparation process of the second slurry is preferably to mix the mica pegmatite concentrate and ultrapure water for slurry preparation.
[0059] In this invention, the volume ratio of liquid nitrogen to the second slurry is preferably 1.5 to 4:1, more preferably 2 to 3:1; the liquid nitrogen quenching time is preferably 24 to 48 hours, more preferably 24 to 36 hours.
[0060] The present invention does not have any particular limitation on the thawing process, and any thawing process well known in the art can be used.
[0061] After thawing, the present invention preferably performs water washing, solid-liquid separation and solid drying on the thawed second slurry in sequence to obtain rapidly cooled mica pegmatite concentrate.
[0062] In this invention, the water washing is preferably neutral; the drying temperature is preferably 60-80°C, more preferably 70-80°C; the drying time is preferably 12-48 hours, more preferably 24-36 hours; the solid-liquid separation is preferably filtration; this invention does not have any special limitation on the filtration, and any filtration process well known in the art can be used.
[0063] During the rapid cooling-thawing process, quartz particles, impurity mineral inclusions, and gas-liquid inclusions are affected by factors such as cold contraction and thermal expansion. The quartz particles break apart, exposing impurities in the crystal lattice, while the inclusions expand and rupture, exposing and vaporizing the impurities within the inclusions, which then diffuse out of the quartz crystal lattice. This process generates numerous cracks on the surface and inside the quartz particles, providing conditions for increasing the contact area during subsequent acid leaching. This invention utilizes a rapid cooling followed by rapid thawing with liquid nitrogen to replace traditional heat treatment methods, causing the quartz particles and their inclusions to break apart and generate cracks. The entire process consumes less energy, is safer to operate, and has less environmental impact. Furthermore, the use of small-molecule acid leaching and nitric acid as an oxidant-assisted leaching, along with the addition of a cation-scavenging agent for acid leaching, significantly increases purification efficiency.
[0064] After obtaining the quenched mica pegmatite concentrate, the present invention mixes the quenched mica pegmatite concentrate, acid, and a second cation capture agent, and performs acid washing treatment to obtain the acid washing leaching product.
[0065] In this invention, the acid solution comprises hydrofluoric acid, hydrochloric acid, and nitric acid; the concentration of the hydrofluoric acid is preferably 0.4–0.6 mol / L, more preferably 0.5 mol / L; the concentration of the hydrochloric acid is preferably 2.5–3.5 mol / L, more preferably 3 mol / L; the concentration of the nitric acid is preferably 0.4–0.6 mol / L, more preferably 0.5 mol / L; the volume ratio of the hydrofluoric acid, hydrochloric acid, and nitric acid is preferably 1:(7.5–15.5):(0.9–2), more preferably 1:(10–15):(1–1.5), and most preferably 1:10:1.5.
[0066] This invention uses small-molecule acids such as hydrofluoric acid to acid wash the sample, allowing hydrogen ions and acid radical ions to diffuse along the cracks in the vein quartz sample into the grain boundaries of the quartz crystal, where they react chemically with impurity minerals, dissolving and diffusing metal ions into the solution. The addition of HNO3 as an oxidant can further assist in the leaching of metal oxides.
[0067] In this invention, the liquid-to-solid ratio of the slurry obtained by mixing the rapidly cooled mica pegmatite concentrate, acid, and the second cation capture agent is preferably 2 to 4:1, and more preferably 3:1.
[0068] In this invention, the second cation scavenger is preferably dodecylamine acetate; the amount of the second cation scavenger added relative to the slurry obtained by mixing the rapidly cooled mica pegmatite concentrate, acid, and the second cation scavenger is preferably 300-500 g / t, more preferably 350-450 g / t.
[0069] In this invention, a cation scavenger is added during the acid washing process. After being rapidly cooled with liquid nitrogen, the cation scavenger comes into contact with quartz particles that have a larger contact area, thereby capturing more Na, K, Li and other ions, and further purifying the quartz sand.
[0070] In this invention, the pickling temperature is preferably 50-80°C, more preferably 60-70°C; the pickling time is preferably 4-12 hours, more preferably 5-10 hours; the pickling is preferably carried out under stirring conditions; the stirring rate is preferably 400-800 rpm, more preferably 500-600 rpm.
[0071] After obtaining the acid leaching product, the present invention washes the acid leaching product sequentially until neutral, performs solid-liquid separation and solid drying to obtain 5N high-purity quartz sand.
[0072] In this invention, the reagent used for washing is preferably water, more preferably ultrapure water; the drying temperature is preferably 60-80°C, more preferably 70-80°C; the drying time is preferably 12-48 hours, more preferably 24-36 hours; the solid-liquid separation is preferably filtration; this invention does not have any special limitation on the filtration, and any filtration process well known in the art can be used.
[0073] In this invention, the mass percentage of SiO2 in the 5N high-purity quartz sand is preferably ≥99.999%, more preferably 99.999%.
[0074] Figure 1 This is a flowchart illustrating the method for preparing 5N high-purity quartz sand using mica pegmatite according to the present invention. Figure 1As shown, this invention involves crushing, grinding, and screening mica pegmatite ore to obtain mica pegmatite powder of varying particle sizes. The powder is then used to adjust the slurry pH, and an ion collector is added. After stirring, the slurry is subjected to flotation to remove impurities, yielding mica pegmatite concentrate. This concentrate is then slurried and rapidly cooled with liquid nitrogen for 24–48 hours. After thawing, the liquid nitrogen-cooled concentrate slurry is acid-washed, and a cation collector is added to further improve quartz purity. After acid washing, the leaching product is washed until neutral, filtered, and dried to obtain 5N high-purity quartz sand.
[0075] This invention uses mica pegmatite as raw material, performs two-stage flotation on the mica pegmatite, and adjusts the pH value to allow OH- to be released. - or H + The distribution of quartz on the surface of mica pegmatite changes, causing it to become charged. In the first stage of flotation, the pulp is adjusted to acidic conditions before adding a cationic scavenger. The negatively charged mica surface effectively increases the adsorption concentration of the scavenger, while the neutral quartz surface reduces electrostatic adsorption with the scavenger, retaining it as much as possible within the flotation cell and minimizing quartz loss. In the second stage of flotation, the pulp is adjusted to neutral or slightly alkaline conditions (7-8) before adding an anionic scavenger to further remove Ti and Fe ions from the first stage flotation, thus purifying the mica pegmatite ore. After obtaining the mica pegmatite concentrate, it is prepared into a pulp and rapidly thawed in liquid nitrogen. During this rapid thawing process, the quartz particles, impurity mineral inclusions, and gas-liquid inclusions are affected by factors such as cold contraction and thermal expansion. The quartz particles break apart, exposing impurities in the crystal lattice, while the inclusions expand and rupture, exposing impurities within the inclusions and causing some to vaporize and diffuse out of the quartz crystal lattice. During this process, numerous fissures are generated on the surface and inside of the quartz particles, providing conditions for increasing the contact area of the quartz particles during subsequent acid washing. Acid washing with small-molecule acids such as hydrofluoric acid allows hydrogen ions and anions to diffuse along the fissures in the fractured quartz sample into the grain boundaries of the quartz crystals, reacting chemically with impurity minerals and dissolving and diffusing metal ions into the solution. The addition of HNO3 as an oxidant assists in the leaching of metal oxides. Simultaneously, a cation scavenger is added during the acid washing process. This cation scavenger contacts the quartz particles, which have a larger contact area, thereby capturing more Na, K, and Li ions. Finally, after solid-liquid separation, water washing, and drying, the quartz sand is purified.
[0076] This invention utilizes a rapid thawing method following liquid nitrogen quenching to replace traditional heat treatment, breaking down quartz particles and their inclusions and creating fissures. The entire process consumes less energy, is safer, and has less environmental impact. Furthermore, the use of small-molecule acid leaching and nitric acid as an oxidizing agent to assist leaching, along with the addition of a cation-scavenging agent for acid washing, significantly increases purification efficiency. This invention is simple, highly controllable, easily scalable, and practical.
[0077] This invention prepares 5N high-purity quartz sand with a SiO2 content of ≥99.999% from mica pegmatite with low SiO2 content, thereby increasing the economic added value of mica pegmatite ore and improving its utilization rate.
[0078] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.
[0079] Example 1
[0080] Mica pegmatite block samples from a certain area in Xinjiang Uygur Autonomous Region were manually selected, crushed by a jaw crusher, and then ground in a planetary ball mill. After grinding, the samples were sieved to obtain raw mica pegmatite powder with a particle size of 75-250 μm.
[0081] In a hanging trough flotation machine, ultrapure water is added to the raw mica pegmatite ore powder to prepare a slurry with a mass of 10 wt.%. After adjusting the slurry for 2 minutes, the pH value of the slurry is adjusted to 2 with a 10 wt.% sulfuric acid solution. Then, 300 g / t of dodecylamine acetate is added, and the mixture is stirred at 1500 rpm for 3 minutes. The bubbles are then manually scraped off with a scraper for 2 minutes. After scraping off the bubbles, the tailings containing mica are discarded to obtain the first impurity-removed slurry.
[0082] After adjusting the pH of the first impurity-removing slurry to 7 with a 10wt.% sodium hydroxide solution, 100g / t of sodium octadecenoate was added for two-stage flotation. The mixture was stirred at 1500rpm for 3min and then manually skimmed with a scraper for 2min. The tailings containing ilmenite were discarded. After washing and filtration, the resulting filter residue was dried at 80℃ for 24h to obtain mica pegmatite concentrate.
[0083] The mica pegmatite concentrate was mixed with ultrapure water to form a 10 wt.% slurry, which was placed in a plastic container and then placed in a liquid nitrogen tank containing twice the volume of liquid nitrogen for rapid cooling. After freezing for 24 hours, the slurry was removed and thawed, then washed with water and filtered. The resulting filter residue was dried at 80°C for 24 hours to obtain the rapidly cooled mica pegmatite concentrate.
[0084] The rapidly cooled mica pegmatite concentrate was mixed with 0.4 mol / L hydrofluoric acid, 2.5 mol / L hydrochloric acid, 0.4 mol / L nitric acid solution, and 300 g / t dodecylamine acetate. The volume ratio of hydrofluoric acid, hydrochloric acid, and nitric acid was 1:10:1.5, resulting in a liquid-to-solid ratio of 3:1. The mixture was stirred at 500 rpm for 6 hours at 60°C. After acid washing, the tailings were discarded, and the quartz sand was washed with ultrapure water until neutral. The filtered quartz sand was then dried at 80°C for 24 hours to obtain 5N high-purity quartz sand.
[0085] Example 2
[0086] Mica pegmatite block samples from a certain area in Xinjiang Uygur Autonomous Region were manually selected, crushed by a jaw crusher, and then ground in a planetary ball mill. After grinding, the samples were sieved to obtain raw mica pegmatite powder with a particle size of 75-250 μm.
[0087] In a hanging trough flotation machine, ultrapure water is added to the raw mica pegmatite ore powder to prepare a slurry with a mass of 20 wt.%. After adjusting the slurry for 2 minutes, the pH value of the slurry is adjusted to 2 with a 10 wt.% sulfuric acid solution. Then, 400 g / t of dodecylamine acetate is added, and the mixture is stirred at 1500 rpm for 3 minutes. The bubbles are then manually scraped off with a scraper for 2 minutes. After scraping off the bubbles, the tailings containing mica are discarded to obtain the first impurity-removed slurry.
[0088] After adjusting the pH of the first impurity-removing slurry to 7.5 with a 10 wt.% sodium hydroxide solution, 150 g / t of sodium octadecenoate was added for two-stage flotation. The mixture was stirred at 1500 rpm for 3 min and then manually skimmed with a scraper for 2 min. The tailings containing ilmenite were discarded. After washing and filtration, the resulting filter residue was dried at 80℃ for 24 h to obtain mica pegmatite concentrate.
[0089] The mica pegmatite concentrate was mixed with ultrapure water to form a slurry of 20 wt.% and placed in a plastic container. The container was then placed in a liquid nitrogen tank containing 3 times its volume of liquid nitrogen for rapid cooling. After freezing for 36 hours, the slurry was removed and thawed. It was then washed with water and filtered. The resulting filter residue was dried at 80°C for 24 hours to obtain the rapidly cooled mica pegmatite concentrate.
[0090] The rapidly cooled mica pegmatite concentrate was mixed with 0.5 mol / L hydrofluoric acid, 3 mol / L hydrochloric acid, 0.5 mol / L nitric acid solution, and 400 g / t dodecylamine acetate. The volume ratio of hydrofluoric acid, hydrochloric acid, and nitric acid was 1:10:1.5, resulting in a liquid-to-solid ratio of 3:1. The mixture was stirred at 500 rpm for 6 hours at 80°C. After acid washing, the tailings were discarded, and the quartz sand was washed with ultrapure water until neutral. The filtered quartz sand was then dried at 80°C for 24 hours to obtain 5N high-purity quartz sand.
[0091] Example 3
[0092] Mica pegmatite block samples from a certain area in Xinjiang Uygur Autonomous Region were manually selected, crushed by a jaw crusher, and then ground in a planetary ball mill. After grinding, the samples were sieved to obtain raw mica pegmatite powder with a particle size of 75-250 μm.
[0093] In a hanging trough flotation machine, ultrapure water is added to the raw mica pegmatite ore powder to prepare a slurry with a mass of 30 wt.%. After adjusting the slurry for 2 minutes, the pH value of the slurry is adjusted to 2.5 with a 10 wt.% sulfuric acid solution. Then, 500 g / t of dodecylamine acetate is added, and the mixture is stirred at 1500 rpm for 3 minutes. The bubbles are then manually scraped off with a scraper for 2 minutes. After scraping off the bubbles, the tailings containing mica are discarded to obtain the first impurity-removed slurry.
[0094] After adjusting the pH of the first impurity-removing slurry to 7.5 with a 10 wt.% sodium hydroxide solution, 200 g / t of sodium octadecenoate was added for two-stage flotation. The mixture was stirred at 1500 rpm for 3 min and then manually skimmed with a scraper for 2 min. The tailings containing ilmenite were discarded. After washing and filtration, the resulting filter residue was dried at 80℃ for 24 h to obtain mica pegmatite concentrate.
[0095] The mica pegmatite concentrate was mixed with ultrapure water to form a slurry of 30 wt.% and placed in a plastic container. The container was then placed in a liquid nitrogen tank containing 4 times its volume of liquid nitrogen for rapid cooling. After freezing for 48 hours, the slurry was removed and thawed. It was then washed with water and filtered. The resulting filter residue was dried at 80°C for 24 hours to obtain the rapidly cooled mica pegmatite concentrate.
[0096] The rapidly cooled mica pegmatite concentrate was mixed with 0.6 mol / L hydrofluoric acid, 3.5 mol / L hydrochloric acid, 0.6 mol / L nitric acid solution, and 500 g / t dodecylamine acetate. The volume ratio of hydrofluoric acid, hydrochloric acid, and nitric acid was 1:10:1.5, resulting in a liquid-to-solid ratio of 3:1. The mixture was stirred at 500 rpm for 12 h at 80 °C. After acid washing, the tailings were discarded, and the quartz sand was washed with ultrapure water until neutral. The filtered quartz sand was then dried at 80 °C for 24 h to obtain 5N high-purity quartz sand.
[0097] Comparative Example 1
[0098] Mica pegmatite block samples from a certain area in Xinjiang Uygur Autonomous Region were manually selected, crushed by a jaw crusher, and then ground in a planetary ball mill. After grinding, the samples were sieved to obtain raw mica pegmatite powder with a particle size of 75-250 μm.
[0099] In a hanging trough flotation machine, ultrapure water is added to the raw mica pegmatite powder to prepare a slurry with a mass of 20 wt.%. After adjusting the slurry for 2 minutes, the pH value of the slurry is adjusted to 2.5 with a 10 wt.% sulfuric acid solution. Then, 400 g / t of dodecylamine acetate is added, and the mixture is stirred at 1500 rpm for 3 minutes. The bubbles are then manually scraped off with a scraper for 2 minutes. The mica-containing tailings are discarded. After washing and filtration, the resulting filter residue is dried at 80℃ for 24 hours to obtain mica pegmatite concentrate.
[0100] The mica pegmatite concentrate after flotation was placed in a crucible and calcined in a muffle furnace at 900℃ for 6 hours. After calcination, the mica pegmatite concentrate was immediately taken out and poured into ultrapure water for water quenching. Then it was washed with ultrapure water and dried at 80℃ for 24 hours to obtain the roasted and water-quenched mica pegmatite concentrate.
[0101] Add 0.5 mol / L hydrofluoric acid, 3 mol / L hydrochloric acid and 0.5 mol / L nitric acid solution to the mica pegmatite concentrate after roasting and water quenching, and stir at 500 rpm for 6 h at 60 °C. After acid washing, discard the tailings, wash the quartz sand with ultrapure water until neutral, filter the quartz sand and dry it at 80 °C for 24 h to obtain high-purity quartz sand.
[0102] Performance testing
[0103] The 5N high-purity quartz sand obtained in Examples 1-3, the high-purity quartz sand obtained in Comparative Example 1, and the raw mica pegmatite ore were analyzed by ICP-MS. The contents of SiO2 and other impurity elements in the quartz sand are shown in Table 1.
[0104] Table 1. Content of SiO2 and other impurity elements in quartz sand
[0105]
[0106] As shown in Table 1, the mass percentage of SiO2 in the 5N high-purity quartz sand prepared by the present invention reaches 99.999%, which is higher than the 99.991% of the high-purity quartz sand obtained in Comparative Example 1. Moreover, the other impurities (Al, Fe, K, Li, Na, B, Ti) in the 5N high-purity quartz sand prepared by the present invention are also much lower than those in the high-purity quartz sand obtained in Comparative Example 1.
[0107] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing 5N high-purity quartz sand using mica pegmatite, characterized in that, Includes the following steps: The first slurry provides raw mica pegmatite powder, and the pH value of the first slurry is 2~3; The first ore slurry is subjected to a first flotation using a first cation scavenger to obtain a first impurity-removed ore slurry; the first cation scavenger is dodecylamine acetate; the amount of dodecylamine acetate added relative to the first ore slurry is 300~500g / t; After adjusting the pH of the first impurity-removing slurry to 7-8, a second flotation is performed on the pH-adjusted first impurity-removing slurry using an anion capture agent to obtain mica pegmatite concentrate; the anion capture agent is sodium octadecenoate; the amount of sodium octadecenoate added relative to the pH-adjusted first impurity-removing slurry is 100-200 g / t; After the mica pegmatite concentrate is prepared into a second slurry, it is sequentially subjected to liquid nitrogen quenching and thawing to obtain quenched mica pegmatite concentrate; the volume ratio of liquid nitrogen to the second slurry is 1.5~4:1; the liquid nitrogen quenching time is 24~48h; The rapidly cooled mica pegmatite concentrate, acid solution, and second cation capture agent are mixed and subjected to acid leaching to obtain the acid leaching product; the acid solution includes hydrofluoric acid, hydrochloric acid, and nitric acid; The acid leaching product was washed sequentially until neutral, then subjected to solid-liquid separation and solid drying to obtain 5N high-purity quartz sand.
2. The method according to claim 1, characterized in that, The pickling temperature is 50~80℃; the pickling time is 4~12h.
3. The method according to claim 1, characterized in that, The liquid-to-solid ratio of the slurry obtained by mixing the rapidly cooled mica pegmatite concentrate, acid, and second cation capture agent is 2-4:
1.
4. The method according to claim 1, characterized in that, The particle size of the mica pegmatite ore powder is 70~300μm.
5. The method according to claim 1 or 4, characterized in that, The mass percentage of mica pegmatite powder in the first slurry is 10-30%.
6. The method according to claim 1, characterized in that, The mass ratio of the anion scavenger to the first cation scavenger is 1:1.5~3.
Citation Information
Patent Citations
Fluoride-free low-acid zwitterion quartz sand reverse flotation process
CN102600982A
Method for producing low-hydroxyl low-gas liquid inclusion high-purity quartz sand
CN109502593A
Method for preparing 4N high-purity quartz sand by taking pegmatite quartz as raw material
CN111874914A